Interferon-gamma Facilitates Neurogenesis by Activating Wnt/β-catenin Cell Signaling Pathway via Promotion of STAT1 Regulation of the β-Catenin Promoter. (10th November 2020) - Yuan, Xianlin; He, Fen; Zheng, Fuxiang; Xu, Yunlong; Zou, Juntao
Highlights: Peripheral IFN-γ stimulation can promote cognitive and behavioral functions in mice. STAT1 binds to the target gene of β-catenin promoter (−218∼−204 bp), which plays a positive regulatory effect on β-catenin. IFN-γ can regulate wnt/β-catenin signaling pathways through STAT1 activation to promote NSCs' proliferation, differentiation. Abstract: Interferon-gamma (IFN-γ) is critical for central nervous system (CNS) functions and it may be a promising treatment to stimulate CNS regeneration. However, previous studies reported inconsistent results, and the molecular mechanisms remain controversial. Here we show that IFN-γ-treated mice via intraperitoneal injection have elevated IFN-γ level in central hippocampus and superior cognitive behaviors IFN-γ could activates the level of protein expression of Wnt7a, β-catenin, and CyclinD1 in Wnt/β-catenin signaling pathway of mice hippocampus. Functional and mechanism analysis in vitro revealed that IFN-γ promoted the proliferation and differentiation in primary cultured neural stem cells (NSCs). STAT1 was accountable for IFN-γ-induced activation of the β-catenin promoter, and IFN-γ increased the binding affinity of STAT1 to β-catenin promoter based on luciferase activity and chromatin immunoprecipitation. Our results suggest that IFN-γ exerts many effects ranging from cognitive function in vivo to NSC proliferation, self-renewal, and differentiation in vitro. It does so by recruiting STAT1 to the β-catenin promoter, enhancing cis-regulation by STAT1, and ultimately activating Wnt/β-catenin signaling. In this study, we first found that STAT1 was recruited into the promoter of β-catenin to activate β-catenin expression, and this effect was regulated by IFN-γ. It is also discovered firstly that Wnt/β-catenin and JAK/STAT pathways form cross-links through STAT1. Promoting neurogenesis through immune stimulation might be a promising strategy for repairing the diseased/injured CNS. This study provides a scientific basis for immunomodulation to promote nerve regeneration and offer a new therapeutic direction for central nervous system regeneration.